Elasto-plastic model of structured marine clay under general loading conditions. (July 2018) - Zhang, Shuo; Ye, Guanlin; Liao, Chencong; Wang, Jianhua
Highlights: A new elastoplastic model is proposed to describe bahavior of structured marine clay under general loading conditions. The true triaxial tests are performed to investigate the mechanical behavior of marine clay under general loading conditions. The effect of intermediate principal stress on strength and deformation can be described simultaneously by the model. By referring to the surperloading surface concept, the influence of structure can also be described by the model. Compared with the Cam-clay model, the model requires only two additional parameters. Abstract: In this paper, we propose an isotropic hardening elastoplastic model for structured marine clay that can describe its strength and deformation behavior under general loading conditions. A series of drained true triaxial tests were performed on structured and remolded marine clay to investigate the effect of intermediate principal stress. The test results show that the intermediate principal stress has a considerable effect, not only on the strength, but also on the deformation behavior of marine clay. A modified stress-dilatancy equation is defined in transformed stress space to capture this feature. Then, the model is extended to consider the influence of structure by incorporating the superloading surface concept. Compared with the modified Cam-Clay model, the proposed model requires only two additional parameters, which can be determined conveniently from triaxial and oedometer tests. The proposed model was validated by performing undrained triaxial tests and drained true triaxial tests at various confining stresses and Lode angles, respectively, on remolded and structured clay.